Factors contributing to early childhood caries (ECC) at the Dental Clinic, Kulliyah of Dentistry, IIUM - Zulkifli, Filzri; Abdul Halim, Amin Fauzi; Harun, Nor Asilah; Ardini, Yunita Dewi (2014)

(untitled)
Objective: To determine the risk factors associated with the occurrence of early childhood caries (ECC) among new paediatric patients at Kulliyyah of Dentistry (KOD), International Islamic University Malaysia (HUM). Materials and methods: A cross-sectional study was conducted from March 2013 to October 2013, among 59 new paediatric patients, 4 and 5-year-old of age, who attended the Polyclinic and Outpatient Clinic, KOD, HUM. The status of dental caries at the surface level was evaluated using World Health Organization (WHO) diagnostic criteria for decayed, missing and filled tooth surfaces (dmfs). A semi-structured questionnaire was used to collect data by interviewing the caregivers. Results: A total of 59 children; 62.8 girls and 37.2 boys, were involved in this study, with mean dmfs value of 13.6. All children were diagnosed with ECC, with 72.2 of 4-year- old and 70.73 of 5-year-old children were found to have severe-early childhood caries (s- ECC). History of sleeping with bottle feeding at night, and not brushing teeth before sleep at night have shown to have an association with the increase in the occurrence of ECC, although the difference was not significant (p>0.05). However, a statistically significant association was found between the high occurrences of ECC with sugary snacking in- between meals and regular consumption of cariogenic drinks (p<0.05). Conclusion: The result showed that sugary snacking in-between meals and cariogenic drinks are the risk factors for ECC at the Dental Clinic, HUM. The occurrence of ECC is associated with a combination of factors; diet, socioeconomic and plaque control management. A new method of effective preventive strategies should be developed to prevent the occurrence of ECC.